Movement regulation in dismounts on the balance beam - Heinen, T.; Frackmann, J.; Müller, A.; Zöllner, V. (Science of Gymnastics Journal, 2024)
In artistic gymnastics, the apparatus structure is considered an essential constraint in regulating gymnastic skill performance under an operating coupling between perception and action. The question arises of how such regulation processes generalize within gymnastic skills with a similar movement goal but a different structure. Therefore, this study aimed to analyze how a particular environmental constraint (i.e., space available on the balance beam) regulates gymnasts` performance in skills with a similar movement goal but a different movement structure. Female gymnasts were asked to perform the round-off and the handspring as dismounts on the balance beam in two conditions (baseline vs. reduced space available). Gymnasts exhibited differences in foot positioning between experimental conditions. For both skills, the most significant part of regulation occurred between the starting point and the first step, and a small part of regulation occurred between the first step and the placement of the hands. While for the round-off, another small part of regulation also occurred between the placement of the second hand and landing on the mat, there was virtually no regulation between the placement of the hands and landing on the mat in the handspring. It is concluded that, for gymnasts, adapting to varying constraints from trial to trial can be seen as an essential skill. Implementing these constraints into practice schedules may help develop a broad range of regulation strategies.